The effects of selenium on tumor growth in epithelial ovarian carcinoma - Park, Jin Sun; Ryu, Ji Yoon; Jeon, Hye-Kyung; Cho, Young Jae; Park, Young Ae; Choi, Jung-Joo; Lee, Jeong-Won; Kim, Byoung-Gie; Bae, Duk-Soo (Journal of gynecologic oncology, 2012)
Epidemiological studies suggest that selenium protects against the development of several cancers. Selenium (sodium selenite) has been reported to interfere with cell growth and proliferation, and to induce cell death. In this study, we tested whether selenium could have growth-inhibiting effect in ovarian cancer cells and an orthotopic animal model. Cell growth in selenium-treated cells was determined in human ovarian cancer cells, A2780, HeyA8, and SKOV3ip1 using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazoliumbromide (MTT) assay. Animal experiment of selenium with paclitaxel was performed using SKOV3ip1 cells in nude mice to evaluate their inhibiting effect for tumor growth. In addition, another animal experiment of paclitaxel with or without selenium was performed to assess the effect of survival and food intake in mice. The in vitro growth of selenium-treated cells was significantly decreased dose-dependently in A2780, HeyA8, and SKOV3ip1 cells. Therapy experiment in mice was started 1 week after injection of the SKOV3ip1 cells. Treatment with selenium (1.5 mg/kg, 3 times/week) and paclitaxel injection showed no addictive effect of the inhibition of tumor growth. However, combination of selenium and paclitaxel showed the slightly increased food intake compared with paclitaxel alone. Although selenium has growth-inhibiting effect in ovarian carcinoma cells in vitro, there is no additive effect on tumor growth in mice treated with combination of paclitaxel and selenium. However, food intake is slightly higher in selenium-treated mice during chemotherapy.